Welfare State Case Study in Indonesia: Legal, Social, and Human Rights Perspectives Towards a Prosperous and Just Society - ., Nursaiti; Kusdarini, Eny (Journal of Posthumanism, 2025)
The welfare state remains a central paradigm in global debates on governance, social justice, and human rights. This article examines the Indonesian welfare state through a multidisciplinary framework that integrates legal, social, and human rights perspectives to assess its role in shaping a just and prosperous society. Using a qualitative case study approach, the study analyzes the relationship between constitutional mandates, legal frameworks, and international human rights obligations and the implementation of social policies in Indonesia. The research findings reveal three important dimensions. First, the Indonesian legal system establishes the normative basis for welfare policies, yet gaps persist in meeting the needs of marginalized groups. Second, persistent inequalities in education, healthcare, and employment highlight challenges to inclusive development. Third, welfare provision must be understood not as a policy preference but as a constitutional and moral obligation of the state. A transformative welfare state requires strong legal instruments, participatory engagement, and a rights-based approach.